Evolutionary diversification and historical biogeography of orchidaceae in Central America with emphasis on Costa Rica and Panama - Bogarín Chaves, Diego Gerardo (2019)
In this thesis, I targeted the orchid genus Lepanthes, one of the six genera of angiosperms that surpasses 1,000 species in the Neotropics, as a study model to investigate the evolutionary processes that promoted species diversifications. To investigate this, we improved the taxonomy of the group integrating a solid phylogenetic framework with morphological evolution, assessing inter-specific relationships in species complexes with hundreds of DNA markers using anchored hybrid enrichment approach, and describing new species. In addition, we addressed the pollination of Trichosalpinx through the study of floral anatomy, pollinator behavior, and floral traits. Trichosalpinx flowers are pollinated exclusively by female biting midges that are attracted by the small quantities of proteins secreted on the flowers. Finally, we inferred the biogeographical history and diversification dynamics of the two largest Neotropical orchid groups (Cymbidieae and Pleurothallidinae), using densely sampled phylogenies coupled with geological datasets and discussed the impact of biogeographical events and orogeny on the species richness of Lepanthes. Species diversification is correlated with Andean orogeny, and multiple migrations and recolonizations across the Andes indicate that mountains do not constrain orchid dispersal over long timescales. This thesis provides new insights into the complex evolution of one of the most species-rich angiosperm.